2007
DOI: 10.1007/s12094-007-0059-7
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly docetaxel and gemcitabine as neoadjuvant chemotherapy followed by adjuvant doxorubicin and cyclophosphamide therapy in stage II and III breast cancer patients: results of a phase II study

Abstract: We consider biweekly docetaxel and gemcitabine could be an active and tolerable regimen option in the neoadjuvant setting sequentially with standard adjuvant doxorubicin-cyclophosphamide in patients with stage II or III breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…This type of complication had been reported with gemcitabine combinations for neoadjuvant treatment in significantly variable rates (10 to 54%), making some authors to advocate for the use of granulocyte stimulating factor during the AG phase, while others do not [9, 13-15, 18, 19] .In our study, the use of weekly paclitaxel seemed not to have potentiated the neutropenic effect, which was more related to the AG combination, as observed in other studies [14,24,25] . Mucositis was much more frequent in our study than reported in other gemcitabine-combination strategies.…”
supporting
confidence: 78%
“…This type of complication had been reported with gemcitabine combinations for neoadjuvant treatment in significantly variable rates (10 to 54%), making some authors to advocate for the use of granulocyte stimulating factor during the AG phase, while others do not [9, 13-15, 18, 19] .In our study, the use of weekly paclitaxel seemed not to have potentiated the neutropenic effect, which was more related to the AG combination, as observed in other studies [14,24,25] . Mucositis was much more frequent in our study than reported in other gemcitabine-combination strategies.…”
supporting
confidence: 78%
“…Furthermore, the combination therapy was advantageous for large or locally advanced breast cancer with respect to breast conservation (76.5%). These results are consistent with the results of a previous neoadjuvant study on patients with stage II–III breast cancer [ 13 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although few reports have assessed the efficacy and safety of the combination of docetaxel and gemcitabine as NAC [ 13 14 ], an overall RR of 71.4% (95% CI, 53.7–85.4), with eight complete and 17 partial responses, was found in a previous neoadjuvant study that enrolled 35 patients with stage II–III breast cancer [ 13 ]. Furthermore, breast conservation was possible in 59% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other common grade III/IV toxicities included thrombocytopenia, anemia, and nausea/vomiting, all with less than a 7% incidence of grade III/IV events. When docetaxel was combined with other drugs every 2 weeks, toxicity profile changed accordingly (Table 4) [22,[29][30][31][32][33][34][35]. Vinorelbine-containing and irinotecan-containing regimens had more myelosuppressive and gastrointestinal toxicity, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 99%